2009
DOI: 10.1590/s0100-54052009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Alterações metabólicas em plantas de feijão originadas de sementes microbiolizadas por Pseudomonas sp. e inoculadas com Xanthomonas axonopodis pv. phaseoli

Abstract: Many enzymes are involved in plant defense a gainst pathogens. T he purpose of this stu dy was to verify altera tions in a ctivity of some enzymes in bea n pla nts origina ted from microbioliza tion of seeds with a fluorescent isolate (DFs84 2) of Pseu do mo na s. Bean seeds (cv. "BRS Valente") were immersed in a bacterial suspension of a 24 hours old Pseudomonas culture (OD 540 =0,5) known as a Xanthomonas axonopodis pv. phaseoli biocontroler. Check treatment consisted of seeds immersed in a saline solution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Increase in FAL is associated with a reduction in the severity of some plant diseases. This was not observed by Silva et al (22), who detected no changes in FAL activity in seed treatment with Bacillus cereus in tomato; however, high peroxidase activity was emphasized. The use of neem (Azadirachta indica) extract promoted an increase in the activity of polifenol oxidase, FAL and peroxidase in carrots, indicating a resistance-inducing effect (17).…”
Section: Resultscontrasting
confidence: 55%
“…Increase in FAL is associated with a reduction in the severity of some plant diseases. This was not observed by Silva et al (22), who detected no changes in FAL activity in seed treatment with Bacillus cereus in tomato; however, high peroxidase activity was emphasized. The use of neem (Azadirachta indica) extract promoted an increase in the activity of polifenol oxidase, FAL and peroxidase in carrots, indicating a resistance-inducing effect (17).…”
Section: Resultscontrasting
confidence: 55%
“…Several authors have reported the biological control of bacterial diseases caused by Xanthomonas spp. (Naue et al, 2014;Halfeld-Vieira et al, 2015;Singh & Siddiqui, 2015), including the selection of biocontroller bacteria against Xap (Zanatta et al, 2007;Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The foliar application of bacterial biocontrol agents could improve the control of common bacterial blight of bean. This is the prospect of some bacterial biocontrol agents that control Xap, selected for the treatment of bean seeds (Zanatta et al, 2007), which could increase the levels of compounds related to resistance (Silva et al, 2009), showing broadspectrum effects (Corrêa et al, 2014). However, there is no information available about the behavior of these bacteria when used in foliar spraying.…”
Section: Introductionmentioning
confidence: 99%